Determination of antioxidant and anti-inflammatory activities, as well as in vitro cytotoxic activities of extracts of Anastatica hierochuntica (Kaff Maryam) against HeLa cell lines - Abou-Elella, Faten; Hanafy, Eman A.; Gavamukulya, Yahaya (Journal of Medicinal Plants Research, 2016)
Anastatica hierochuntica L. is distributed throughout the Arabian Peninsula, and North Africa. It is locally called "Kaff Maryam". All parts of the plant are used in folk medicine. This study aimed to investigate possible antioxidant activity of various extracts of Kaff Mariam, anti-inflammatory activities, as well as in vitro cytotoxic activities. Five extract types were used, namely, the whole ethanolic extracts, ethyl acetate, petroleum ether, water, and butanol extracts. The explored items included determination of total phenolics using the Folin-Ciocalteu assay and total flavonoids using Muller’s method, anti-oxidant activity using three assays (2, 2'-Azinobis [3-ethylbenzothiazoline-6-sulfonic acid]- diammonium salt (ABTS), reducing power, and 2, 2-diphenyl-1-picrylhydrazyl (DPPH)), membrane stabilization test for anti-inflammatory studies, as well as in vitro cytotoxic activities against HeLa cell lines using the 3-(4, 5-dimethylthiozol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. The results obtained indicated high flavonoid and phenolic contents in all the five extracts types. All extracts registered high antioxidant activity using three assays, but generally, the ABTS assay recorded the highest antioxidant activity as compared to the reducing power and DPPH methods. The membrane stabilization test showed that extracts of Kaff Maryam had good anti-inflammatory activity. Extracts of Kaff Maryam also registered very good cytotoxic activities against HeLa cell lines. Kaff Maryam extracts have good antioxidant, anti-inflammatory, and cytotoxic activities and the results of this study provide the basis for further investigation of Kaff Maryam for potential identification of novel bioactive compounds with therapeutic properties.
Keywords: Anastatica hierochuntica; Kaff Maryam; Antioxidants; Anti-inflammatory; HeLa cell lines; Cytotoxicity